Efficacy and Safety of Revacept, a Novel Lesion-Directed Competitive Antagonist to Platelet Glycoprotein VI, in Patients Undergoing Elective Percutaneous Coronary Intervention for Stable Ischemic Heart Disease: The Randomized, Double-blind, Placebo-Controlled ISAR-PLASTER Phase 2 Trial - Mayer, Katharina; Hein-Rothweiler, Ralph; Schupke, Stefanie; Janisch, Marion; Bernlochner, Isabell; Ndrepepa, Gjin; Sibbing, Dirk; Gori, Tommaso; Borst, Oliver; Holdenrieder, Stefan; Kupka, Danny; Petzold, Tobias; et al. (JAMA Cardiology, 2021)
Importance: The assessment of new antithrombotic agents with a favorable safety profile is clinically relevant. Objective: To test the efficacy and safety of revacept, a novel, lesion-directed antithrombotic drug, acting as a competitive antagonist to platelet glycoprotein VI. Design, Setting, and Participants: A phase 2 randomized clinical trial; patients were enrolled from 9 centers in Germany from November 20, 2017, to February 27, 2020; follow-up ended on March 27, 2020. The study included patients with stable ischemic heart disease (SIHD) undergoing elective percutaneous coronary intervention (PCI). Interventions: Single intravenous infusion of revacept, 160 mg, revacept, 80 mg, or placebo prior to the start of PCI on top of standard antithrombotic therapy. Main Outcomes and Measures: The primary end point was the composite of death or myocardial injury, defined as an increase in high-sensitivity cardiac troponin to at least 5 times the upper limit of normal within 48 hours from randomization. The safety end point was bleeding type 2 to 5 according to the Bleeding Academic Research Consortium criteria at 30 days. Results: Of 334 participants (median age, 67.4 years; interquartile range, 60-75.1 years; 253 men [75.7%]; and 330 White participants [98.8%]), 120 were allocated to receive the 160-mg dose of revacept, 121 were allocated to receive the 80-mg dose, and 93 received placebo. The primary end point showed no significant differences between the revacept and placebo groups: 24.4%, 25.0%, and 23.3% in the revacept, 160 mg, revacept, 80 mg, and placebo groups, respectively (P =.98). The high dose of revacept was associated with a small but significant reduction of high-concentration collagen-induced platelet aggregation, with a median 26.5 AU × min (interquartile range, 0.5-62.2 AU × min) in the revacept, 160 mg, group; 43.5 AU × min (interquartile range, 22.8-99.5 AU × min) in the revacept, 80 mg, group; and 41.0 AU × min (interquartile range, 31.2-101.0 AU × min) in the placebo group (P =.02), while adenosine 5′-diphosphate-induced aggregation was not affected. Revacept did not increase Bleeding Academic Research Consortium type 2 or higher bleeding at 30 days compared with placebo: 5.0%, 5.9%, and 8.6% in the revacept, 160 mg, revacept, 80 mg, and placebo groups, respectively (P =.36). Conclusions and Relevance: Revacept did not reduce myocardial injury in patients with stable ischemic heart disease undergoing percutaneous coronary intervention. There were few bleeding events and no significant differences between treatment arms. Trial Registration: ClinicalTrials.gov Identifier: NCT03312855.
CRIS-Team Scopus Importer:2023-03-08